The things they carried [compact disc, unabridged] - O'Brien, Tim, 1946- (Recorded Books, 2003)
This depicts the men of Alpha Company. They battle the enemy (or maybe more the idea of the enemy), and occasionally each other. In their relationships we see their isolation and loneliness, their rage and fear. They miss their families, their girlfriends and buddies; they miss the lives they left back home. Yet they find sympathy and kindness for strangers (the old man who leads them unscathed through the mine field, the girl who grieves while she dances), and love for each other, because in Vietnam they are the only family they have.